Perubahan Lingkungan dan Konflik Kekerasan Membaca Papua Melalui Pendekatan Environmental Security - Ucu Martanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Though many researchers haue been incorporated enaironment and natural resources aspects in their analysis to understand prolong conflict in Papua-Indonesia, their reports seem flaw and vogue in determining the linkages between enaironment (and natural resources) and aiolent conflicts. It creates ambiguous and weak proposals to resolae complex and multidimensional conflict in Papua. This article propose theoretical framework, often used in developing countries, to understand and interprete empirical phenomenon on enaironmental induced conflict in Papua. Enaironmental scarcity theory elaborates the causes of environmental induced conflict in three dimensions: the causes of environmental scarcity, the social effects, and the type of conflicts.